Spectral Variations And Physical Conditions Of By Draconis In The Ultraviolet - Sanad, M. R.
We present International Ultraviolet Explorer (IUE) observations during the period (1980 - 1994) of the double lined spectroscopic binary BY Dra to show the spectral behavior and physical conditions in its atmosphere. Представлены наблюдения IUE спектрально-двойной звезды BY Dra в период с 1980 по 1994 гг. с целью показать спектральное поведение и физические условия в её атмосфере.
Keywords: Астрофизика